Analisis Marketing Digital Merek Skincare Npure di Instagram - Fatiha Aizza Adzra; Maya Amalia Oesman Palapah (UNISBA Press, 2024)
Abstract. Skincare NPure has many fans in Indonesia. One way for NPure to market its products is through the digital platform Instagram. NPure uses the reels service to sell its products. One of their Instagram upload is titled